Oligo-Carrageenan Kappa Increases Glucose, Trehalose and Tor-P and Subsequently Stimulates the Expression of Genes Involved in Photosynthesis, and Basal and Secondary Metabolisms in Eucalyptus Globulus - Zuniga-Navarro, G; Moenne-Munoz, A; Laporte-Poblete, D; Contreras-Arredondo, R; Gonzalez-Figueroa, A; Saucedo-Aguiar, S; Gomez-Luna, M (BioMed Central Ltd., 2019)
Background: It has been previously shown that oligo-carrageenan (OC) kappa increases growth, photosynthesis and activities of enzymes involved in basal and secondary metabolisms in Eucalyptus globulus. However, it is not known whether OC kappa may induce the activation of TOR pathway and the increase in expression of genes encoding proteins involved in photosynthesis and enzymes of basal and secondary metabolisms. Results: E. globulus trees were sprayed on leaves with water (control) or with OC kappa 1 mg mL- 1, once a week, four times in total, and cultivated for 17 additional weeks (21 weeks in total). Treated trees showed a higher level of net photosynthesis than controls, beginning at week 3, a higher height, beginning at week 9, and those differences remained until week 21. In addition, treated trees showed an increase in the level of glucose beginning at week 1, trehalose at weeks 1-3, and in TOR-P level at week 1-2. On the other hand, transcripts encoding proteins involved in photosynthesis, and enzymes involved in glucose accumulation, C, N and S assimilation, and synthesis of secondary metabolites began at weeks 3-4 and with additional peaks at weeks 5-6, 8-11,13-14 and 17-19. Thus, OC kappa induced initial increases in glucose, trehalose and TOR-P levels that were followed by oscillatory increases in the level of transcripts coding for proteins involved in photosynthesis, and in basal and secondary metabolisms suggesting that initial increases in glucose, trehalose and TOR-P may trigger activation of gene expression. Conclusions: The stimulation of growth induced by OC kappa in E. globulus trees is due, at least in part, to activation of TOR pathway and the increase in expression of genes encoding proteins involved in photosynthesis and enzymes of basal metabolism. © 2019 The Author(s).